2015
DOI: 10.14434/josotl.v15i2.12825
|View full text |Cite
|
Sign up to set email alerts
|

Is Twitter a Pedagogical Tool in Higher Education? Perspectives of Education Graduate Students

Abstract: This study presents the perspectives of education graduate students of using Twitter as a pedagogical tool for 15 weeks as a required social media activity in class. The results indicated that each course participants reported a positive learning experience of using Twitter. Although this was their first experience with Twitter, participants reported that Twitter provided space and opportunities to engage in academic activities as a new pedagogical tool. Participants reported they used Twitter to receive immed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 11 publications
(16 reference statements)
4
70
0
5
Order By: Relevance
“…This result is consistent with that of Gao et al (2012), who claimed that the informal nature of microblogging sites does not detract from their promotion and support of language learning. Some other studies underlined the potential of Twitter to be a convenient environment that positively affects language learning and education (Mork, 2009;Harmandaoglu, 2012;Gao et al, 2012;Bista, 2015;Mompean & Fouz-González, 2016;Antenos-Conforti, 2009;Borau et al, 2009;Elfatah & Ahmed, 2015). In an exploration of Twitter as an avenue for learning, Borau et al (2009) found that the site provides individuals suitable opportunities to practise language use.…”
Section: Social Media As Learning Toolsmentioning
confidence: 99%
“…This result is consistent with that of Gao et al (2012), who claimed that the informal nature of microblogging sites does not detract from their promotion and support of language learning. Some other studies underlined the potential of Twitter to be a convenient environment that positively affects language learning and education (Mork, 2009;Harmandaoglu, 2012;Gao et al, 2012;Bista, 2015;Mompean & Fouz-González, 2016;Antenos-Conforti, 2009;Borau et al, 2009;Elfatah & Ahmed, 2015). In an exploration of Twitter as an avenue for learning, Borau et al (2009) found that the site provides individuals suitable opportunities to practise language use.…”
Section: Social Media As Learning Toolsmentioning
confidence: 99%
“…Twitter is among the 10 most popular online social networks, integrating a community of over 500 million users around the world. Twitter has already been used in several educational programs and evaluated as a positive teaching experience with an outstanding potential in academic and educational environments (1–6). However, there are scarce examples available in the literature about its use in science teaching and communication.…”
Section: Introductionmentioning
confidence: 99%
“…Bista (2015) studied the perceptions of education graduate students on using Twitter as a pedagogical tool during class activities. Similarly, Lin et al (2013) conducted a qualitative case study to examine the uses of Twitter when implemented as a supplement to online and face-to-face classroom learning among graduate students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The majority of the current literature focuses on examining social media use and integration within formal educational settings (e.g., Allen & Nelson, 2013;Bista, 2015;Gao, Luo, & Zhang, 2012;Lin, Hoffman, & Borengasser, 2013), and little attention has been paid to how graduate departments or programs use social media in informal ways. While it is not uncommon for graduate departments or programs to have an institutional social media presence, the instructional design (ID) field has a limited understanding of how our programs use social media.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation